Domperidone for increasing breast milk volume in mothers expressing breast milk for their preterm infants: a systematic review and meta‐analysis. (27th March 2018) - Grzeskowiak, LE; Smithers, LG; Amir, LH; Grivell, RM
Abstract : Background: Mothers of preterm infants often struggle to produce enough breast milk to meet the nutritional needs of their infant. Galactagogues such as domperidone are often prescribed to increase breast milk supply but evidence supporting their role in clinical practice is uncertain. Objective: To evaluate the efficacy and safety of domperidone for increasing breast milk volume in mothers expressing breast milk for their preterm infants. Search strategy: MEDLINE, Embase and Web of Science were searched without language restrictions from first publication until January 2017. Bibliographies of articles and reviews were hand‐searched for additional reports. Selection criteria: Randomised controlled trials that compared domperidone with placebo in mothers of preterm infants (<37 weeks' gestation) experiencing insufficient milk supply. Data collection and analysis: Two review authors independently assessed studies for inclusion, extracted data and evaluated study quality. Differences in breast milk volume and adverse events were combined using fixed effects meta‐analysis. Main results: The pooled analysis of five trials consisting of 194 women demonstrated a moderate increase in daily breast milk volume of 88.3 ml/day (95% CI 56.8–119.8) with the use of domperidone compared with placebo. No difference was evident with respect to maternal adverse events (odds ratio 1.05, 95% CI 0.65–1.71), with no reported cases of prolonged QTc syndrome or sudden cardiac death. Sensitivity analyses showed no important differences in the estimates of effects. Conclusions: Domperidone is well tolerated and results in a moderate short‐term increase in expressed breast milk volume among mothers of preterm infants previously identified as having insufficient breast milk supply. Tweetable abstract: Domperidone leads to short‐term improvements in breast milk volume in mothers of preterm infants. Tweetable abstract: Domperidone leads to short‐term improvements in breast milk volume in mothers of preterm infants. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights15177